Prospective study to evaluate the functional and radiological outcome of intra-articular fractures of distal end humerus fixed with dual plating - Shahu, Yogesh Kumar; Rajak, Manoj; Thakur, Rajesh; Singh, Anoop; Gupta, Raj Kumar (International Journal of Research in Orthopaedics, 2025)
Background: Distal humerus fractures, however rare in adults, pose significant surgical problems due to their intricate anatomy and articular involvement. For functional motion, AO type C intra-articular fractures need stable fixation. Despite scant Indian evidence, dual-plate osteosynthesis is commonly used. Methods: A prospective observational study at Tata Main Hospital, Jamshedpur, patients with AO type C distal humerus fractures. Each was open reduced and internally fixed with dual plating (orthogonal or parallel). Radiological combination was described by joining three cortices and functional outcomes were measured by the Mayo Elbow Performance Score (MEPS). After the Shapiro–Wilk test showed that the data were normal, statistical analysis was done. Results: Mean age: 49.5±12.5 years and 51.6% of them were women. Falls were the main cause of most AO type C2 fractures (51.6%). MEPS was much higher in people younger than 60 than in people older than 60 (p=0.016). Mean MEPS was highest for C1 fractures and lowest for C3 fractures (p=0.068), but there was no link between the two that was significant. As many as 80.6% of the results were good or excellent. Conclusions: Dual-plate fixation effectively reduces AO type C distal humerus fractures, enabling early mobilization and improved function. Younger age improves prognosis, but fracture complexity does not. Prospective design and standardized evaluation are study strengths, but small sample size and restricted follow-up are weaknesses. Multicentric trials should be larger.